Outcome of tension free open mesh repair of inguinal hernia (Journal of Surgical Sciences, 2020)
Background: In the practice of General Surgery, hernia repair is the second most common procedure after appendectomy. Several methods have been developed over the years to try to improve hernia repair. Good result can be expected using Bassini's, McVay's, Shouldice's techniques provided the exact nature of hernia is recognized and the repair is done without tension using healthy tissue. The introduction of synthetic mesh started a new era in hernia surgery. The use of synthetic mesh repair of primary and recurrent hernias has gradually gained acceptance among surgeons.Objective: To find out the outcome and complications of open inguinal hernia repair with prolene mesh.Methods: This is a prospective cross sectional study conducted at Bangabandhu Sheikh Mujib Medical University (BSMMU), Dhaka, from December, 2011 to May, 2012. One hundred patients of inguinal hernia admitted in different surgical units of BSMMU, Dhaka for elective surgery were studied. We have given 1 gm ijv Cephradine per operatively and then 500 gm cephradine ijv 6 hourly for 24 hours followed by oral form of Cephradine for next 5 days. Polypropylene mesh of 11 cm x 7 cm size was used in all cases. All the operations were done by open tension free prolene mesh repair technique. Patients were followed for one year to see the outcome.Results: Out of 100 cases of inguinal hernia, 71 patients (71%) had indirect inguinal hernia and 29 cases (29%) had direct inguinal hernia; 90 cases (90%) were primary hernia and only 10 cases (10%) were recurrent hernia; 58 cases were right sided, 34 cases (34%) were left sided and 8 cases (8%) were bilateral. Complications of mesh repair of groin hernia in this study included wound infection (5%), scrotal oedema (2%), mesh infection (0%), scrotal hematoma (2%), echymoces of peri-incisional skin (5%), early wound and groin pain (7%), chronic inguinodynia (2%), hernia recurrence (1%).Conclusion: In the present study an attempt is made to evaluate the outcome of patients undergoing inguinal hernia repair by prolene mesh. The results confirm that Lichtenstein tension free mesh repair of inguinal hernia is safe and reliable for both primary and recurrent groin hernia, with less recurrence rate. Patient's compliance was good with minimum morbidity.Journal of Surgical Sciences (2018) Vol. 22 (1): 21-24